MODAL SOSIAL MASJID UNTUK PEMBERDAYAAN KEUMATAN - Romo H. R. Muhammad Syafii (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2024)
Social capital collected through the mosque instrument can be used as a source of community empowerment efforts. The mosque is not only positioned as a place to carry out ritual activities of devotion but is also intended for managing community issues related to the interests of the community's livelihood, as well as the interest in analyzing the extent of the strengths and weaknesses of the community in responding to various social situations that surround it. Through the concept of social capital, it was found that the social strength of the community is not only born and arises from external encouragement, but more than that, it arises and is motivated by the traditions and teachings of Islam itself. In fact, this internal encouragement is quite strong because it is based on ideological motivation. Through regulatory support, economic centers and community empowerment can be specifically diverted and managed by the mosque as the vanguard. This is what can be done by focusing on the performance of zakat, infaq and sedekah, as well as baitul maal which are managed professionally and modernly through the mosque instrument.